Sustainable Costs Based on the Wisdom Value 'Melopei' in the Metompa Ada Tradition of the Mori Impo Tribe - Sudamara, Jenalda; Abdul, Abdul Kahar; Paranoan, Selmita; Sugianto, Sugianto (Universitas KH. Abdul Chalim Mojokerto, 2026)
This ethnographic study investigates sustainable cost practices in the Melopei ritual of the Mori impo tribe's Metompa Ada marriage tradition in North Morowali Regency, Central Sulawesi. Through participant observation and in-depth interviews with four key informants, this research examines how traditional costs integrate economic, social, environmental, and spiritual dimensions. The Melopei ritual involves three symbolic fortresses with progressive payments (IDR 150,000, IDR 120,000, and IDR 100,000 respectively) plus a long batik cloth, representing the groom's readiness to build a household. These costs function not as mere expenses but as social investments that legitimize marriage and honor women's dignity. The symbolism is profound: the first two fortresses represent respect for breasts as sources of nourishment, while the third honors the womb as the origin of life. The findings demonstrate that Melopei operates as a traditional social accounting system incorporating profit (economic readiness), people (kinship strengthening), planet (sustainable resource use), and spirituality (recognition of life's sanctity). This research concludes that indigenous cost practices offer a more holistic sustainability accounting framework than the conventional Triple Bottom Line, enriching global accounting discourse with culturally-grounded perspectives.